THE ARTISTIC FORMATION AND LINGUOCULTURAL ESSENCE OF THE “STEPMOTHER” IMAGE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article provides a comprehensive analysis of the artistic formation and linguocultural essence of the “stepmother” image in world literature and folklore. The study examines historical, social, and cultural factors that contributed to the emergence of this archetype, as well as its transformation in modern literary discourse. Special attention is given to the linguistic representation of the stepmother figure and its reflection in phraseological units, metaphors, and cultural narratives. The findings demonstrate that the stepmother image functions as both a universal and culturally specific phenomenon, deeply embedded in collective consciousness and language.